IMPLEMENTASI PROGRAM KAMPUNG KB SEBAGAI INOVASI STRATEGIS PENCEGAHAN 4T (4 TERLALU) DALAM KEHAMILAN DI RW 10 MARGADANA, TEGAL - Seventina Nurul Hidayah; Ulfatul Latifah (JURNAL KEBIDANAN, 2018)
Today many women do not know when is the right time to start getting pregnant and cannot be pregnant again. The situation is too 4 (young, old, close and many) to be an internal factor of the mother which affects the complications of pregnancy and childbirth which have an impact on AKI and AKB. This research was based on the declaration of a KB village in RW 10 Margadana Village. The purpose of this study is to analyze the implementation of the KB Village program in RW 10 Margadana Village. This research is qualitative using descriptive method. Data collection was carried out by in-depth interview techniques in accordance with interview guidelines. The results of interviews were recorded and made field notes with a research model using a model on Public Policy Implementation developed by George C. Edward III. The results of the research showed that from four indicators of the program, two of them have been achieved well, namely disposition and bureaucracy structure, this was because in the implementation of the program of Kampung KB, the program executor and the target were already maximum. Yet the indicators of resources have not met the requirements because of the inadequate facilities. Among the obstacles in the implementation of Kampung KB program were communication from the local government cannot unite related agencies, namely the population and health services, insufficient budgets and the lack of participation and awareness of the community in RW 10 Margadana village. The researcher recommended suggestions: the posts of Kampung KB are to be made specifically for activities related to family planning,, and in the socialization, the BKKBN (National Population and Family Planning Board) Lampung should motivate the community to participate in the implementation of Kampung KB program in RW 10 Margadana Village.